Identification and genetic study of lactic acid bacteria from intestine of domestic chickens (Gallus gallus domesticus) - Ixora Sartika Mercuriani; Heru Nurcahyo; Bernadetta Octavia; Astuti Astuti; Adinda Yuslia Rukmanandita; Fita Nilasari (Universitas Gadjah Mada, 2025)
The gastrointestinal tract is one of the habitats of lactic acid bacteria (LAB). This research aims to identify the LAB isolated from the intestines of domestic chickens (Gallus gallus domesticus) based on phenotypic and genotypic characteristics. The LAB was cultivated on enrichment media MRSA + CaCO3 1% and a selection of isolates based on the halo zone. The phenotypic character identification using morphological, physiological and biochemical tests was analyzed by similarity simple matching (SSM) and a dendrogram (MVSP 3.1). Genotypic identification was made by 16S rRNA gene sequences with PCR methods, sequencing and analysis using BLAST at www.ncbi.nlm.nih.gov. The results show that 87 isolates were isolated based on the halo zone. Phenotypic tests were performed on eight isolates (J6, J15, J18, J28, B11, B24, B25 and B26). The results show that four isolates have similarities with the genus Bacillus, two isolates with the genus Lactobacillus, and two with the genus Streptococcus. The identification based on the 16S rRNA gene of four selected isolates (J15, J28, B24 and B26) showed that J15 was identified as Bacillus cereus (98.56% similarity); J28 as Lactobacillus johnsonii (99.67%); B24 as Bacillus cereus (98.30%), and B26 as Streptococcus pluranimalium (96.68%).